Silsilah Al-Żahāb Dalam Ṣaḥīḥ Al-Bukhārī - Umar, Subehan Khalik; Ansari, Mujaddid (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2022)
Silsilah al-żahab or the golden path of narration is a theoretical development of aṣaḥ al-asānīd. This theory was born on the basic assumption that in the transmission of hadith there are several figures from the companions, tabi’in and tabi’ tabiin who are proven to have several narrations in one series. Qualitative methods are used to reassess the level of validity of the narration pathways in question and make the opinions of scholars in the book of rijāl al-ḥadīṡ a benchmark for assessment. It was found that Imām al-Bukhārī had established the genealogy of narration which his successors knew as aṣaḥ al-asānīd or silsilah al-żahab. Of course, the existence of this lineage of al-żahab does not deny the strict conditions in assessing the validity of a narration. Imam al-Bukhārī has set the conditions for muāsyarah between teachers and students in terms of receiving and giving history and instead on the situation of the relationship between teacher and student in the form of face-to-face and social interaction.